1998
DOI: 10.1111/j.1471-0528.1998.tb10207.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes in insulin resistance in human pregnancy: longitudinal study with the hyperinsulinaemic euglycaemic clamp technique

Abstract: Objective To perform measurements of insulin resistance serially in pregnancy and after childbirth in normal women.Design Longitudinal study. Setting Teaching hospital.Methods Ten normal women were studied using the hyperinsulinaemic euglycaemic clamp technique before pregnancy, at 16, 26 and 36 weeks gestation, and 8 weeks after delivery. All women breastfed their infants. Insulin resistance was measured by the glucose infusion rate required to maintain the plasma glucose at 4.5 mmoyl.Results There was a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 19 publications
(26 reference statements)
4
46
2
Order By: Relevance
“…These findings therefore suggest that there is progressive rise in insulin secretion as the pregnancy advances, indirectly signifying an increase in IR as the pregnancy advances. Similar finding had been reported by Stanley K et al, [12]. Catalano P et al, found significant 65% increase in both basal insulin and C-peptide concentrations in all subjects with advancing gestation [22].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings therefore suggest that there is progressive rise in insulin secretion as the pregnancy advances, indirectly signifying an increase in IR as the pregnancy advances. Similar finding had been reported by Stanley K et al, [12]. Catalano P et al, found significant 65% increase in both basal insulin and C-peptide concentrations in all subjects with advancing gestation [22].…”
Section: Discussionsupporting
confidence: 89%
“…Available literature [12][13][14] suggests that there is a rise in IR in 3 rd trimester of pregnancy. However literature is less on the 1 st and 2 nd trimester.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the gestational period examined in this study is before the time when most of the physiological insulin resistance of pregnancy occurs, 35 so the insulin resistance that we detected may, in some cases, have already existed before the pregnancy. This has important future therapeutic implications.…”
Section: Perspectivesmentioning
confidence: 99%
“…Pregnancy is related to glucose metabolism disorders and insulin resistance (Hadden and McLaughlin, 2009;Johnson, 2008;Stanley et al, 1998). Insulin resistance may facilitate supply of appropriate nutrients particularly of glucose to fetus for fetal growth and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Resistin is another protein identified recently as a hormone secreted by adipocytes which has a controversial history regarding its role in the pathogenesis of obesity-mediated insulin resistance and type 2 diabetes (Lu et al, 2006;Hasegawa et al, 2005;Hivert et al, 2008). Insulin sensivity changes from an enhanced state during early pregnancy to an insulin resistant state in late pregnancy (Kirwan et al, 2002;Leturque et al, 1984;Stanley et al, 1998). Therefore it is inspected, subsequent to increase in IR during pregnancy, its related factors change, too.…”
Section: Introductionmentioning
confidence: 99%